Synthesis towards O-linked AFGP analogues with lactose as its carbohydrate component - Gong, Ruoying (University of Ottawa (Canada), 2009)
Antifreeze glycoproteins (AFGPs) are biological antifreezes which are found in the blood serum of arctic fish to help them living in the subzero temperature environments. AFGPs have a common structure composed with a carbohydrate and a peptide moiety by alpha O-linkage and can inhibit ice recrystallization which is useful in medical and commercial applications. The alpha O-linkage is very sensitive to acidic, basic and enzymatic conditions, therefore design and synthesizing AFGP analogues are more attractive. Thermal hysteresis (TH) and IRI activities of AFGPs have no relationship with one another and antifreeze analogues having good IRI and no TH will be good candidates for cryopreservation. Recent reports suggested that hydration numbers and hydration indices of carbohydrates are important factors for its antifreeze activity. Antifreezes having saccharides with high hydration number and hydration index show good IRI activities which are in accordance with antifreeze activities of the saccharides. My research goal was to synthesize 53 which is a truncated version of compound 52 (originally synthesized by Nishimura group) and test its IRI activity. Lactose has a high hydration number and hydration index in disaccharides and shows a good recrystallization inhibition. If compound 53 has good IRI activity, we can then conclude that the IRI activities of AFGP analogues which have disaccharides as their carbohydrate moiety are in accordance with the recrystallization inhibition activities of their carbohydrate moiety themselves. The compound 53 was synthesized through a convergent method. In its carbohydrate component synthesis, the glycosyl donor, benzyl ether protected lactose fluoride 55 was prepared starting from commercially available lactose. The synthesis of peptide component 56 was started from commercially available N-Fmoc-O-t-butyl-L-threonine 61. Coupling reaction between 55 and 56 and then deprotecting the allyl ether to obtain the building blocks 54 and 65. The glycopeptides 68 and 72 were obtained from standard SPPS. Following cleaved 68 and 72 from the solid support, the final products should be obtained from removing their benzyl groups. Unfortunately, the debenzylation could not be achieved, and the final polymer 69 and 73 were not obtained.
Keywords: Chemistry, Organic.